GREYWATER MANAGEMENT OF PANTAI BARU PANDANSIMO KABUPATEN BANTUL FOR CREATING ZERO WASTE ZONE - Agung Eka Saputra; Arif Kusumawanto; Siti Syamsiah (ASEAN Journal of Systems Engineering, 2015)
The beach which is experiencing the current developments in the districts of Bantul is Pantai Baru Pandansimo. This area is an area that has been declared by the Bantul regent as zero waste zone. The development of Pantai Baru Pandansimo will give some impact. Thing that can arises is the environmental pollution from trading activity at restaurants around Pantai Baru Pandansimo. Every restaurant produce washing waste (greywater) had only absorbed into the ground or yard restaurants because do not have access to treatment plant.          The main objective of this research is plan alternative system management for greywater that corresponding to Pantai Baru Pandansimo area so can creating sustainable zero waste zone. The results of the analysis obtained that alternative management unit greywater that appropriate and can be used at Pantai Baru Pandansimo is subsurface constructed wetland  because easy to understand society and easy maintenance. Application of processing units that had been planned to reduce the BOD load in the amount of 41% depending on the extent of the unit to be used and reduce greywater is discharged into the environment 60% -80% of waste. From calculations obtained, wetland unit dimensions used by the average discharge within one week of 276.25 liters / day is 1 x 0.5 x 0.8 m3 with detention time (td) 0,5 day. Wetland that is used can be used as a park around the culinary of Pantai Baru Pandansimo and can encourage people to be more aware of the concept of zero waste.